Adenocarcinoma mimicking appendicular lump: a diagnostic dilemma—a case report. Issue 1 (December 2016) - Kalpande, Sanket; Pandya, Jayashri; Sharma, Tushar
Abstract Background Primary appendiceal adenocarcinoma is a rare tumor, mucinous variety being common. This case is reported to highlight the unusual presentation and diagnostic difficulty of appendiceal adenocarcinoma. Case presentation Patient presented with acute appendicitis with ill-defined tender lump which responded to conservative management. Conclusions High index of suspicion should be kept in mind for elderly patients presenting with appendicular lump. Every effort should be made during elective appendectomy to remove stump in case of sloughed out appendix.